Problem Based Learning Strategy Models at Islamic Universities - Siti Nurbaya (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2025)
This paper aims to analyze Problem-Based Learning (PBL) learning strategy models in Islamic universities. This study uses a qualitative method with a literature study approach, then analyzed starting from data reduction, data presentation, and drawing conclusions. To ensure valid data, this study uses source triangulation to find different gaps while obtaining accurate and consistent data. The findings indicate that the PBL learning model in Islamic universities is rooted in two main frameworks: the Problem-Based Learning model by Bransford and Stein and the Problem-Solving Learning model of the troubleshooting type proposed by David H. Jonassen. In its implementation, both models develop adaptively through self-directed learning, collaborative, and scaffolding approaches. Furthermore, this study provides a new contribution by showing that the implementation of PBL in Islamic universities is not only oriented towards cognitive aspects, but also integrates religious and ethical values ​​in the learning process. These findings confirm that PBL is a flexible, contextual learning model, and has great potential in developing critical and reflective thinking skills, while also shaping students' character holistically.